Implementación del repositorio documental con búsqueda inteligente para el Departamento Gestión de la Calidad UNACH utilizando plataformas de colaboración empresarial - Padilla Delgado, Carmen Amelia (2025)
The access, storage, and efficient management of institutional documentation represent a key aspect for academic and administrative success in public institutions of higher education. In this context, the Quality Management Department of the Universidad Nacional de Chimborazo (UNACH) identified the need for an organized system to centralize information related to institutional processes. This need motivated the development of the present research project, whose main objective was to implement a document repository with intelligent search capabilities, using enterprise collaboration platforms such as Microsoft SharePoint. The system implementation aimed to optimize the storage and retrieval of information related to macroprocesses, subprocesses, procedures, forms, manuals, and guidelines used by the institution. This was intended to improve document traceability, facilitate efficient searches for specific files, and strengthen quality management at the university. To carry out the project, the Kanban methodology was used, allowing for a visual and flexible management of development tasks, promoting iterative work and real-time progress monitoring. Additionally, a chatbot was integrated as a complement to the system, aimed at facilitating access to stored documentation by enabling users to perform intelligent searches based on their needs. As part of the system validation, a survey was conducted with end users to evaluate its functionality, based on the ISO 9241-11 standard, which considers three key indicators: satisfaction, effectiveness, and efficiency. The results showed a score of 179 in satisfaction, 174 in effectiveness, and 170.2 in efficiency.